FACTORS INFLUENCING SUSTAINABILITY OF FOOD AND BEVERAGE FRANCHISEE’S BUSINESSES IN MALAYSIA - Samsudin, Fauziah; Che Razak, Razli; Yasin, Nurul Hafizah Mohd (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The growth of the franchise business in Malaysia has significantly contributed to the national economy, amounting to approximately RM30.03 billion of the Malaysian gross domestic products (GDP), compared to RM10.02 billion in 2009. However, in terms of GDP percentage contribution, the results have been inconsistent. According to the International Franchise Association (2022), approximately 32,700 franchised businesses in Malaysia shut down within the first six months following the COVID-19 outbreak as of August 2020. Without major government advocacy, it is predicted that another 36,000 franchised units may not survive. Previously, the Malaysian government aimed to increase the number of franchise outlets from 10,720 in 2010 to 76,010 outlets in 2020, with an expected creation of 150,800 jobs and a projected GDP growth contribution of 9.4% (KPDNKK, 2016). To sustain this growth in the 21st century, franchise entrepreneurs must foster sustainable creative value while navigating the challenges of an evolving business environment and adapting to the global innovation process. Both internal and external limitations affect business survivability. This paper aims to explore franchise models by analysing different dimensions and strategies related to franchise business sustainability goals. Agency Theory, Resource-Based View (RBV) Theory, and Contingency Theory are integrated to examine the potential relationships between key variables and to develop a comprehensive research framework. A total of 241 franchisee companies from the food and beverage sector in Malaysia participated in this study. Data was collected through surveys and analysed using SPSS and Partial Least Squares (PLS) procedures to test the study’s hypotheses. This study contributes to both theoretical and practical knowledge by offering a robust research framework. It provides a clear understanding of the impact of selected variables as strategic factors influencing franchisee business sustainability. The findings can be beneficial for companies and academicians in developing effective strategies for the franchise industry.